ANALISIS PERAN PARA PIHAK DALAM PENGELOLAAN DAERAH ALIRAN SUNGAI BENGAWAN SOLO HULU - C Yudi Lastiantoro; S Andy Cahyono (Centre for Research and Development on Social, Economy, Policy and Climate Change, 2015)
Public participation increasingly required in resouces management decision-making. Necessary understanding of who affected by decisions, and who had the power to influence and interest to decision. The purpose of this study was to analyze the role of the parties in the management of the Upper Bengawan Solo Watershed. The study was conducted in the Upper Bengawan Solo Watershed which located in Wonogiri District using qualitative approach and stakeholder analysis methods. The results indicated that there were number of stakeholders who had a major interest and influence in the success of watershed management. Duties and functions determined the degree of influence and interests of the institution. This implies that policy makers in watershed management should take into account their aspirations in achieving successul of Upper Solo watershed management. Coordination is necessary in order to avoid overlap, duplication, and achievement of goals.